2021
DOI: 10.3390/cancers13030466
|View full text |Cite|
|
Sign up to set email alerts
|

Macrophage and Lymphocyte Infiltration Is Associated with Volumetric Tumor Size but Not with Volumetric Growth in the Tübingen Schwannoma Cohort

Abstract: Most patients with vestibular schwannomas can be cured with microsurgical resection, or tumor growth can be stabilized by radiotherapy in certain cases. Recurrence is rare but usually difficult to treat. Treatment alternatives to local therapies are not established. There is growing evidence of the role of inflammatory processes in schwannomas, which may be exploitable by targeted innovative therapies. To further define the impact of inflammation with tumor growth in vestibular schwannoma, we performed immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 28 publications
4
15
0
Order By: Relevance
“…Although the composition varies with each tumor, immune cells can infiltrate the TME and take on several roles that promote and/or resist inflammation and tumor proliferation. 24 Although the mechanisms have not been fully elucidated, several studies have found associations between TAMs, tumor growth, and HL in VS. 5 , 22 , 25 - 28 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the composition varies with each tumor, immune cells can infiltrate the TME and take on several roles that promote and/or resist inflammation and tumor proliferation. 24 Although the mechanisms have not been fully elucidated, several studies have found associations between TAMs, tumor growth, and HL in VS. 5 , 22 , 25 - 28 …”
Section: Discussionmentioning
confidence: 99%
“… 21 , 28 , 29 Because of differences in how tumor growth was measured across studies, it remains unclear from these investigations whether macrophage infiltration is actually protective and slows the dynamic volumetric tumor growth rate. 28 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations